HUMAN CAPITAL CHALLENGES IN INDONESIA AND WELCOME ASEAN ECONOMIC COMMUNITY (AEC) in 2015 - Muhamad Rizal (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
Charter and ASEAN blueprint towards the ASEAN Economic Community (AEC) in 2015, has been agreed by the members, characterized by a new round of joint commitment that is legally binding. AEC Blueprint will give direction of ASEAN as a regional production base and single market. The blueprint is supported by the five essential pillars namely: the free flow of goods, services, investment, skilled labor, and freer flow of capital. Efforts to realize the ASEAN as a regional production base and single market is certainly provides a lot of great opportunities and challenges for Indonesia. In this regard, the main sectors which require improvement are professional human capital and competent. Without improvements in this sector, efforts to achieve the Indonesian government for human capital to compete with other countries in Southeast Asia will be difficult. Therefore, in facing such competition, the Indonesian government should prepare a Human Resources (HR) were skilled, intelligent and competitive that Indonesian human resources able to compete.